Effectiveness of chest physiotherapy in stabilizing respiratory rate among pediatric patients with acute respiratory infection - Yohan Trayanus Djaha; Maria Kurni Menga; Wibowo (Edukasi Ilmiah Indonesia, 2025)
Introduction: Acute Respiratory Infection (ARI) remains one of the leading causes of morbidity and mortality among children, particularly in developing countries. It often results in respiratory distress due to mucus accumulation and inflammation. Chest physiotherapy is a non-pharmacological intervention that helps mobilize bronchial secretions, improve lung ventilation, and reduce respiratory effort. Methods: This case study was conducted on two hospitalized preschool-aged children (3–6 years old) diagnosed with ARI at Sandi Karsa Hospital, Makassar. Chest physiotherapy consisting of percussion, vibration, and postural drainage was administered once daily for three consecutive days. Respiratory rate was measured before and after each intervention session using a stopwatch and observation sheet. Results: The findings revealed a consistent decrease in respiratory rate following each physiotherapy session. Both patients showed an average reduction of 2–3 breaths per minute after therapy, indicating improved respiratory stability. The children also demonstrated decreased signs of dyspnea and greater comfort after treatment. No adverse effects were observed during or after the intervention. These results suggest that chest physiotherapy effectively facilitates mucus clearance, enhances ventilation, and stabilizes breathing frequency in pediatric ARI patients. Conclusion: Chest physiotherapy is an effective and safe non-invasive nursing intervention for improving respiratory rate stability in children with ARI. Its implementation can be integrated into hospital nursing care protocols as supportive therapy to accelerate recovery and enhance patient comfort, particularly in managing mild to moderate respiratory infections.